Preparation method of carbon nanofiber loaded platinum-based nanoparticles

The preparation of carbon nanofiber-supported platinum-based nanoparticles by electrospinning and high-temperature pyrolysis methods has solved the problem of insufficient oxygen reduction reaction activity and stability of existing platinum-based materials, achieved efficient and stable electrocatalytic performance of oxygen reduction reactions, and reduced catalyst costs.

CN119581590APending Publication Date: 2025-03-07NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411760566.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing platinum-based materials are insufficient in oxygen reduction electrocatalysts, which limits their application in hydrogen fuel cells and metal air batteries.

Method used

The carbon nanofiber-loaded platinum-based nanoparticles PtNi@PNCF were prepared by electrospinning combined with high-temperature pyrolysis. By controlling the high-temperature pyrolysis process and heteroatom-doped carbon nanofibers as support, the platinum-based alloy nanoparticles were uniformly supported to generate abundant catalytic active sites.

Benefits of technology

The electrocatalytic activity and stability of the oxygen reduction reaction of PtNi@PNCF is significantly improved, the utilization rate of precious metals is improved, the cost of the catalyst is reduced, and the catalytic performance of the oxygen reduction reaction is shown in the acidic medium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581590A_ABST
    Figure CN119581590A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of carbon nanofiber loaded platinum-based nanoparticles, which comprises the following steps: 1, heating N, N-dimethylformamide, adding polyacrylonitrile, and stirring to form a solution; 2, adding chloroplatinic acid hexahydrate, nickel nitrate hexahydrate and triphenylphosphine into the solution, and stirring to obtain a precursor solution; 3, performing electrostatic spinning on the precursor solution to obtain a fibrous precursor; 4, freeze-drying the fibrous precursor; and 5, carrying out pyrolysis reduction on the freeze-dried fibrous precursor. The carbon nanofiber loaded platinum-based nano-particles are prepared by adopting a method of combining electrostatic spinning with high-temperature pyrolysis, the carrier with high specific surface area and rich pore structures is obtained, the interaction between the carrier and the platinum-based alloy nano-particles is enhanced, rich catalytic active sites are generated, and the catalytic activity of the platinum-based alloy nano-particles is improved. The oxygen reduction reaction electrocatalytic activity and stability of the PtNi-coated PNCF are improved, and the PtNi-coated PNCF is suitable for being used as an oxygen reduction reaction electrocatalyst of a fuel cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of carbon-supported platinum-based alloy materials, and in particular relates to a method for preparing carbon nanofiber-supported platinum-based nanoparticles. Background Art

[0002] Regulating the surface structure of platinum-based materials at the atomic level is crucial for the development of efficient oxygen reduction reaction electrocatalysts for renewable energy storage systems. Currently, commercial Pt / C catalysts have low precious metal utilization and insufficient stability when operating in acidic solutions, which leads to the inability to promote them in practical applications, thus hindering their application in the fields of hydrogen fuel cells and metal-air batteries. In order to reduce the cost of the catalyst and further improve the catalytic efficiency, carbon carriers with large specific surface area and rich pore structure can be designed, and the uniformity of platinum-based active sites on the carrier can be regulated to improve the utilization of active sites. Studies have found that the electrocatalytic oxygen reduction reaction activity and stability of platinum-based catalysts can be improved by preparing platinum-nickel and platinum-iron alloys, so that they can effectively improve the efficiency of electrocatalytic oxygen reduction reaction. In addition, people have also adjusted the electrocatalytic performance of platinum-based alloy nanoparticles by controlling the size of platinum-based alloy nanoparticles, and obtained platinum-based alloy electrocatalysts uniformly dispersed on carbon carriers. How to rationally regulate the electronic structure and surface structure of porous carbon-supported platinum-based catalysts to enhance the electrocatalytic activity and stability of platinum-based materials in oxygen reduction reactions is a challenge for current research. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a method for preparing carbon nanofiber-loaded platinum-based nanoparticles in view of the deficiencies of the above-mentioned prior art. The method adopts a method of electrospinning combined with high-temperature pyrolysis to prepare carbon nanofiber-loaded platinum-based nanoparticles PtNi@PNCF, so that platinum-based alloy nanoparticles are uniformly loaded on the surface of heteroatom-doped carbon nanofibers, generating abundant catalytic active sites, improving the electrocatalytic activity and stability of PtNi@PNCF in oxygen reduction reactions, and solving the problem of insufficient electrocatalytic activity and stability of existing platinum-based materials in oxygen reduction reactions.

[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing carbon nanofiber-loaded platinum-based nanoparticles, characterized in that the method comprises the following steps:

[0005] Step 1: Heat N,N-dimethylformamide DMF to 40°C to 50°C, then add polyacrylonitrile PAN, and stir magnetically to form a uniformly dispersed solution;

[0006] Step 2: adding chloroplatinic acid hexahydrate, nickel nitrate hexahydrate and triphenylphosphine to the solution formed in step 1, maintaining the temperature at 40° C. to 60° C. and stirring continuously for 4 h to 8 h to obtain a precursor solution;

[0007] Step 3, transferring the precursor solution obtained in step 2 into a syringe for electrospinning, and collecting the fibrous precursor;

[0008] Step 4: freeze-drying the fibrous precursor collected in step 3 to obtain a freeze-dried fibrous precursor;

[0009] Step 5: placing the freeze-dried fibrous precursor obtained in step 4 in a tubular furnace, performing a pyrolysis reduction treatment in a mixture of hydrogen and argon, and obtaining a black product after natural cooling, which is the carbon nanofiber-loaded platinum-based nanoparticles.

[0010] The above-mentioned method for preparing carbon nanofiber-loaded platinum-based nanoparticles is characterized in that the mass ratio of N,N-dimethylformamide DMF to polyacrylonitrile PAN in step 1 is 10 to 30: 1. Preferably, the mass ratio is 10 to 20: 1. The present invention is conducive to the smooth progress of the electrospinning process by controlling the raw material ratio.

[0011] The above-mentioned method for preparing a carbon nanofiber-supported platinum-based nanoparticle is characterized in that the amount of chloroplatinic acid hexahydrate and nickel nitrate hexahydrate added in step 2 is 1:2-4 according to the molar ratio of Pt to Ni, the mass ratio of triphenylphosphine to polyacrylonitrile PAN in step 1 is 1-4:10, and triphenylphosphine is added after chloroplatinic acid hexahydrate and nickel nitrate hexahydrate are completely dispersed in the solution. The present invention controls the amount of chloroplatinic acid hexahydrate, nickel nitrate hexahydrate and triphenylphosphine added to ensure that an appropriate amount of phosphorus is introduced to effectively change the electronic structure of platinum, generate Pt-P bonds, produce a strong synergistic ligand effect on platinum-based nanoparticles, and then improve the electrocatalytic activity.

[0012] The above-mentioned method for preparing carbon nanofibers loaded with platinum-based nanoparticles is characterized in that during the electrospinning in step three, the voltage applied between the syringe needle and the aluminum foil collector is 18kV to 20kV, and the distance between the syringe needle and the aluminum foil collector is 9cm to 15cm.

[0013] The above-mentioned method for preparing a carbon nanofiber loaded with platinum-based nanoparticles is characterized in that the process of the pyrolysis reduction treatment in step 5 is: the heating rate is 2°C / min to 5°C / min, first the temperature is raised to 180°C and kept for 1 hour, and then the temperature is raised to 700°C to 900°C and kept for 1 hour to 3 hours. In the pyrolysis reduction treatment process of the present invention, the temperature is first raised to 180°C and kept for 1 hour, which helps to stabilize the fiber material structure and ensure that the carbon nanofiber maintains its morphology and performance in the subsequent high-temperature treatment, and then the temperature is raised to 700°C to 900°C and kept for 1 hour to 3 hours. By controlling the temperature to prevent the aggregation of platinum-based nanoparticles, it helps to maintain the dispersibility and stability of the nanoparticles. At the same time, the pyrolysis process further improves the electronic transmission performance of the product, and forms a stable carbon nanofiber structure after high-temperature pyrolysis reduction treatment, thereby having excellent conductivity and mechanical properties.

[0014] The above-mentioned method for preparing carbon nanofiber-loaded platinum-based nanoparticles is characterized in that the carbon nanofiber-loaded platinum-based nanoparticles obtained in step five are ground and prepared into catalyst ink, and an electrocatalytic oxygen reduction reaction test is carried out; the electrocatalytic oxygen reduction reaction test adopts an electrochemical workstation three-electrode system, with Ag / AgCl as the reference electrode, a graphite electrode as the counter electrode, and a glassy carbon electrode coated with the catalyst ink as the working electrode, and is carried out in a 0.1M HClO4 acidic solution.

[0015] Compared with the prior art, the present invention has the following advantages:

[0016] 1. The present invention adopts an electrospinning method to synthesize a polyacrylonitrile supramolecular polymer containing metal platinum, nickel atoms and triphenylphosphine, and then pyrolyzes and reduces the precursor at high temperature in a hydrogen-argon mixed gas to obtain carbon nanofiber-loaded platinum-based nanoparticles PtNi@PNCF. The high-temperature pyrolysis reduction process is controlled to control grain growth and grain boundary diffusion, and the doped carbon nanofibers are used as carriers to enhance the electronic interaction with platinum-based alloy nanoparticles, thereby improving the particle size uniformity of platinum-based nanoparticles, so that size-controllable platinum-based alloy nanoparticles are uniformly loaded on the surface of heteroatom-doped carbon nanofibers, generating abundant catalytic active sites, which is beneficial to improving the oxygen reduction reaction electrocatalytic activity of PtNi@PNCF.

[0017] 2. The present invention adopts the method of electrospinning combined with high-temperature pyrolysis to prepare a carbon nanofiber carrier, which has a high specific surface area and rich pore structure, which is beneficial to improving the charge transfer and material transport in the electrochemical reaction process, and further enhances the electrocatalytic activity of PtNi@PNCF in the oxygen reduction reaction; at the same time, the carbon nanofiber carrier is doped with heteroatoms, which enhances the interaction between the carrier and the platinum-based alloy nanoparticles, and enhances the durability of PtNi@PNCF.

[0018] 3. The low-loading platinum-based alloy nanoparticles prepared by the present invention are not only small in size, which improves the utilization rate of precious metals and reduces the cost of catalysts, but also optimize the electronic structure of Pt through the electronic effect between Pt and Ni atoms, and change the adsorption of oxygen-containing intermediates on the surface of PtNi@PNCF, thereby improving the catalytic performance of oxygen reduction reaction in acidic media.

[0019] 4. The preparation method of the present invention is simple and controllable with high yield. The prepared PtNi@PNCF has the synergistic effect of fast electron / ion transport and multiple active centers. The main active sites contain platinum-nickel alloy, pyridine nitrogen and graphite nitrogen. It is used as an electrocatalyst for the oxygen reduction reaction of fuel cells and exhibits excellent electrocatalytic activity and stability for the oxygen reduction reaction.

[0020] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a flow chart of the preparation process of the PtNi@PNCF material of the present invention.

[0022] Figure 2 This is the TEM image of the PtNi@PNCF material prepared in Example 1 of the present invention.

[0023] Figure 3 This is the XRD pattern of the PtNi@PNCF material prepared in Example 1 of the present invention.

[0024] Figure 4 This is the X-ray photoelectron spectrum (XPS) diagram of the PtNi@PNCF material prepared in Example 1 of the present invention.

[0025] Figure 5 This is a test diagram of the electrocatalytic oxygen reduction reaction performance of the PtNi@PNCF material prepared in Example 1 of the present invention in 0.1M HClO4 acidic solution.

[0026] Figure 6 This is a stability test diagram of the PtNi@PNCF material prepared in Example 1 of the present invention in 0.1M HClO4 acidic solution. DETAILED DESCRIPTION

[0027] Example 1

[0028] like Figure 1 As shown, this embodiment includes the following steps:

[0029] Step 1: Heat 20 g of N,N-dimethylformamide (DMF) to 50°C, then add 1 g of polyacrylonitrile (PAN) and stir magnetically to form a uniformly dispersed solution;

[0030] Step 2: Add 0.5 mM chloroplatinic acid hexahydrate, 2 mM nickel nitrate hexahydrate and 1.525 mM triphenylphosphine to the solution formed in step 1, and add triphenylphosphine after chloroplatinic acid hexahydrate and nickel nitrate hexahydrate are completely dispersed in the solution, and stir continuously at 60° C. for 6 hours to obtain a precursor solution;

[0031] Step 3: Transfer the precursor solution obtained in step 2 to a syringe for electrospinning. The voltage applied between the syringe needle and the aluminum foil collector is 20 kV, the distance between the syringe needle and the aluminum foil collector is 9 cm, and the injection rate of the precursor solution is 0.006 mL min -1 , collecting and obtaining a fibrous precursor;

[0032] Step 4: freeze-drying the fibrous precursor collected in step 3 to obtain a freeze-dried fibrous precursor;

[0033] Step 5. Place the freeze-dried fibrous precursor obtained in step 4 in a tubular furnace and perform thermal reduction treatment in a mixed gas of hydrogen and argon in a volume ratio of 1:9: the heating rate is 5°C / min, first heated to 180°C and kept warm for 1h, then heated to 800°C and kept warm for 2h, and after natural cooling, a black product is obtained, which is carbon nanofiber-loaded platinum-based nanoparticles (PtNi@PNCF material).

[0034] Figure 2 TEM image of the PtNi@PNCF material prepared in this example. Figure 2 It can be seen that the platinum-based nanoparticles with a particle size of less than 5 nm in the carbon nanofiber-loaded platinum-based nanoparticles are uniformly loaded on the surface of the carbon nanofiber.

[0035] Figure 3 This is the XRD pattern of the PtNi@PNCF material prepared in this example. Figure 3 It can be seen that after thermal reduction, the characteristic peak position of Pt(111) (corresponding number in the standard library is PDF#04-08-2) shifted, and the characteristic peak of PtP2 (corresponding number in the standard library is PDF#80-2220) appeared, indicating that P atoms were successfully introduced into the Pt lattice.

[0036] Figure 4 This is the X-ray photoelectron spectroscopy (XPS) diagram of the PtNi@PNCF material prepared in this example. Figure 4 It can be seen that heteroatoms and metal atoms are successfully introduced into the carbon nanofiber structure.

[0037] After grinding the PtNi@PNCF material prepared in this embodiment, 4 mg was dispersed in 1 mL of isopropanol (0.5% Nafion) solution, and continuous ultrasonic treatment was performed for 30 min to prepare catalyst ink, and an electrocatalytic oxygen reduction reaction test was performed; the electrocatalytic oxygen reduction reaction test used an electrochemical workstation three-electrode system, with Ag / AgCl as the reference electrode, a graphite electrode as the counter electrode, and a glassy carbon electrode with 9 uL of catalyst ink dropped on it as the working electrode, and was performed in a 0.1 M HClO4 acidic solution.

[0038] Figure 5 This is a test diagram of the electrocatalytic oxygen reduction reaction performance of the PtNi@PNCF material prepared in this example in a 0.1M HClO4 acidic solution. Figure 5 It can be seen that the half-wave potential of the carbon nanofiber-loaded platinum-based nanoparticles is 0.878 V and the limiting current density is -5.79 mA cm -2 .

[0039] Figure 6 This is a stability test diagram of the PtNi@PNCF material prepared in this example in a 0.1M HClO4 acidic solution. Figure 6 It can be seen that the carbon nanofibers loaded with platinum-based nanoparticles still maintain a relatively high current density after 20,000 seconds.

[0040] In summary, the PtNi@PNCF material prepared in the present invention has outstanding catalytic activity and stability in redox reaction (ORR).

[0041] Example 2

[0042] like Figure 1 As shown, this embodiment includes the following steps:

[0043] Step 1: Heat 10 g of N,N-dimethylformamide (DMF) to 50°C, then add 1 g of polyacrylonitrile (PAN), and stir magnetically to form a uniformly dispersed solution;

[0044] Step 2: Add 0.5 mM chloroplatinic acid hexahydrate, 1.5 mM nickel nitrate hexahydrate and 0.763 mM triphenylphosphine to the solution formed in step 1, and add triphenylphosphine after chloroplatinic acid hexahydrate and nickel nitrate hexahydrate are completely dispersed in the solution, and stir continuously at 60° C. for 4 hours to obtain a precursor solution;

[0045] Step 3: Transfer the precursor solution obtained in step 2 to a syringe for electrospinning. The voltage applied between the syringe needle and the aluminum foil collector is 19 kV, the distance between the syringe needle and the aluminum foil collector is 12 cm, and the injection rate of the precursor solution is 0.005 mL min -1, collecting and obtaining a fibrous precursor;

[0046] Step 4: freeze-drying the fibrous precursor collected in step 3 to obtain a freeze-dried fibrous precursor;

[0047] Step 5. Place the freeze-dried fibrous precursor obtained in step 4 in a tubular furnace and perform thermal reduction treatment in a mixed gas of hydrogen and argon in a volume ratio of 1:9: the heating rate is 3°C / min, first heated to 180°C and kept warm for 1h, then heated to 900°C and kept warm for 1h, and after natural cooling, a black product is obtained, which is carbon nanofiber-loaded platinum-based nanoparticles (PtNi@PNCF material).

[0048] Example 3

[0049] like Figure 1 As shown, this embodiment includes the following steps:

[0050] Step 1: Heat 30 g of N,N-dimethylformamide (DMF) to 50° C., then add 1 g of polyacrylonitrile (PAN) and stir magnetically to form a uniformly dispersed solution;

[0051] Step 2: Add 0.5 mM chloroplatinic acid hexahydrate, 1 mM nickel nitrate hexahydrate and 0.38 mM triphenylphosphine to the solution formed in step 1, and add triphenylphosphine after chloroplatinic acid hexahydrate and nickel nitrate hexahydrate are completely dispersed in the solution, and stir continuously at 60° C. for 8 h to obtain a precursor solution;

[0052] Step 3: Transfer the precursor solution obtained in step 2 to a syringe for electrospinning. The voltage applied between the syringe needle and the aluminum foil collector is 18 kV, the distance between the syringe needle and the aluminum foil collector is 15 cm, and the injection rate of the precursor solution is 0.005 mL min -1 , collecting and obtaining a fibrous precursor;

[0053] Step 4: freeze-drying the fibrous precursor collected in step 3 to obtain a freeze-dried fibrous precursor;

[0054] Step 5. Place the freeze-dried fibrous precursor obtained in step 4 in a tubular furnace and perform thermal reduction treatment in a mixed gas of hydrogen and argon in a volume ratio of 1:9: the heating rate is 2°C / min, first heated to 180°C and kept warm for 1h, then heated to 700°C and kept warm for 3h, and after natural cooling, a black product is obtained, which is carbon nanofiber-loaded platinum-based nanoparticles (PtNi@PNCF material).

[0055] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing carbon nanofiber-loaded platinum-based nanoparticles, characterized in that: The method comprises the following steps: Step 1: Heat N,N-dimethylformamide DMF to 40°C to 50°C, then add polyacrylonitrile PAN, and stir magnetically to form a uniformly dispersed solution; Step 2: adding chloroplatinic acid hexahydrate, nickel nitrate hexahydrate and triphenylphosphine to the solution formed in step 1, maintaining the temperature at 40° C. to 60° C. and stirring continuously for 4 h to 8 h to obtain a precursor solution; Step 3, transferring the precursor solution obtained in step 2 into a syringe for electrospinning, and collecting the fibrous precursor; Step 4: freeze-drying the fibrous precursor collected in step 3 to obtain a freeze-dried fibrous precursor; Step 5: placing the freeze-dried fibrous precursor obtained in step 4 in a tubular furnace, performing a pyrolysis reduction treatment in a mixture of hydrogen and argon, and obtaining a black product after natural cooling, which is the carbon nanofiber-loaded platinum-based nanoparticles.

2. The method for preparing carbon nanofiber-loaded platinum-based nanoparticles according to claim 1, characterized in that: The mass ratio of N,N-dimethylformamide DMF to polyacrylonitrile PAN in step 1 is 10-30:

1.

3. The method for preparing carbon nanofiber-loaded platinum-based nanoparticles according to claim 1, characterized in that: The amounts of chloroplatinic acid hexahydrate and nickel nitrate hexahydrate added in step 2 are calculated based on a molar ratio of Pt to Ni of 1:2-4, the mass ratio of triphenylphosphine to polyacrylonitrile PAN in step 1 is 1-4:10, and triphenylphosphine is added after chloroplatinic acid hexahydrate and nickel nitrate hexahydrate are completely dispersed in the solution.

4. The method for preparing carbon nanofiber-loaded platinum-based nanoparticles according to claim 1, characterized in that: During the electrospinning in step 3, the voltage applied between the syringe needle and the aluminum foil collector is 18 kV to 20 kV, and the distance between the syringe needle and the aluminum foil collector is 9 cm to 15 cm.

5. The method for preparing carbon nanofiber-loaded platinum-based nanoparticles according to claim 1, characterized in that: The process of the pyrolysis reduction treatment in step 5 is: the heating rate is 2°C / min to 5°C / min, first heating to 180°C and keeping it for 1 hour, then heating to 700°C to 900°C and keeping it for 1 hour to 3 hours.

6. The method for preparing carbon nanofiber-supported platinum-based nanoparticles according to claim 1, characterized in that: The carbon nanofiber-loaded platinum-based nanoparticles obtained in step five are ground into catalyst ink and subjected to an electrocatalytic oxygen reduction reaction test; the electrocatalytic oxygen reduction reaction test uses an electrochemical workstation three-electrode system, with Ag / AgCl as a reference electrode, a graphite electrode as a counter electrode, and a glassy carbon electrode drop-coated with the catalyst ink as a working electrode, and is carried out in a 0.1M HClO4 acidic solution.